Preconditions for the Economic Development of the Jewelry Industry and Its Legal Aspects in the Republic of Kazakhstan - YDYRYS, Serikbay Saduakasuly; MUNASIPOVA, Malike Erehankizi (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
This paper assesses the contemporary state of the jewelry industry in Kazakhstan. It also gives a comparative analysis of the development of this sector in Kazakhstan and the developed countries. The present research identifies the main problems constraining its development and the priorities in the context of industrialization. It develops the effective measures for the development of this sector in Kazakhstan.